2015
DOI: 10.1093/mnras/stv051
|View full text |Cite
|
Sign up to set email alerts
|

An early phase of environmental effects on galaxy properties unveiled by near-infrared spectroscopy of protocluster galaxies at z > 2

Abstract: This work presents the results from our near-infrared spectroscopy of narrow-band selected Hα emitters (HAEs) in two rich overdensities (PKS 1138-262 at z=2.2 and USS 1558-003 at z = 2.5) with the Multi-Object Infrared Camera and Spectrograph (MOIRCS) on the Subaru telescope. These protoclusters are promising candidates for the most massive class of galaxy clusters seen today (Paper I). The confirmed HAEs in the protoclusters at z > 2 show high excitation levels as characterized by much higher [Oiii]/ Hβ or [O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 119 publications
(295 reference statements)
9
85
5
Order By: Relevance
“…However, this iscontroversial given several contradictory cases, such as higher metallicity (e.g., Steidel et al 2014;Shimakawa et al 2015), a flat mass-metallicity relation (thus, higher metallicity in lower mass regime, e.g., Kulas et al 2013), and the same mass-metallicity relation as fields (e.g., Tran et al 2015) at z∼2. Therefore, we stick to the general comprehension of the stellar mass-metallicity relation.…”
Section: Co(3-2) To Gas Massmentioning
confidence: 99%
“…However, this iscontroversial given several contradictory cases, such as higher metallicity (e.g., Steidel et al 2014;Shimakawa et al 2015), a flat mass-metallicity relation (thus, higher metallicity in lower mass regime, e.g., Kulas et al 2013), and the same mass-metallicity relation as fields (e.g., Tran et al 2015) at z∼2. Therefore, we stick to the general comprehension of the stellar mass-metallicity relation.…”
Section: Co(3-2) To Gas Massmentioning
confidence: 99%
“…At higher redshifts, the dependence of metallicity on environment is not clear. Kulas et al (2013) and Shimakawa et al (2015) both report that proto-cluster galaxies at z ∼ 2 exhibit metallicity enhancements compared to field galaxies at those redshifts; Valentino et al (2015) report opposite trends. The samples at high redshifts are small and may be subject to selection effects and systematic measurement uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Besides ordinary galaxies, very rare objects, such as Lyα blobs, submillimeter galaxies (SMGs), and active galactic nuclei (AGNs), are also frequently discovered in highdensity environments (Lehmer et al 2009;Digby-North et al 2010;Tamura et al 2010;Matsuda et al 2011). Some contradictory results in the mass-metallicity relation have been revealed among protoclusters at the same redshift (Kulas et al 2013; Kacprzak et al 2015;Shimakawa et al 2015;Valentino et al 2015). Furthermore, Cucciati et al (2014) have found a large amount of cold gas surrounding a z = 2.9 protocluster, which may serve as the reservoir for significant future star formation.…”
Section: Introductionmentioning
confidence: 99%